Penyuluhan pemanfaatan sumber daya lokal di Dusun Kontar: Pelatihan pembuatan pupuk organik cair dari bonggol pisang (Musa paradisiaca): Extension on the use of local resources in Kontar Village: Training for manufacturing liquid organic fertilizer from banana (Musa paradisiaca) corm - Anwar Anwar; Haisyah Haisyah; Permi Kabisatio AS.; Wiwi Sawira; Aco Iham Belman; Hildawati Hildawati; Muhammad Fahyu Sanjaya (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2024)
One of the problems in Kontar Hamlet in Botto Village, Campalagian District, Polewali Mandar Regency is the abundance of banana trees in house yards and in community gardens, causing many unused banana stems to become waste. To overcome this problem, the community service team from the Agrotechnology Study Program, Faculty of Agriculture and Forestry, University of West Sulawesi conducted counseling and technical guidance regarding the processing of banana tuber waste into liquid organic fertilizer which can be utilized by farming communities in Kontar Hamlet, Botto Village, Campalagian District for applying to cultivated plants. The aim of implementing this outreach program is to provide direct understanding and training to the community regarding the management of banana tuber waste into liquid organic fertilizer which so far has not been utilized optimally due to lack of information and minimal knowledge of the local community. The method for implementing this activity is by providing direct counseling and training to the people of Kontar Hamlet. The results of this activity are organic fertilizer made from banana tubers and can be used for plant growth. Apart from that, around 90% of the community has understood the concept of liquid organic fertilizer during counseling, and around 80% of the community has known the process of managing banana corms into liquid organic fertilizer during training.